2020
DOI: 10.1038/s41598-020-79181-6
|View full text |Cite
|
Sign up to set email alerts
|

Bile accelerates carcinogenic processes in pancreatic ductal adenocarcinoma cells through the overexpression of MUC4

Abstract: Pancreatic cancer (PC) is one of the leading causes of mortality rate globally and is usually associated with obstructive jaundice (OJ). Up to date, there is no clear consensus on whether biliary decompression should be performed prior to surgery and how high levels of serum bile affects the outcome of PC. Therefore, our study aims were to characterise the effect of bile acids (BAs) on carcinogenic processes using pancreatic ductal adenocarcinoma (PDAC) cell lines and to investigate the underlying mechanisms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…3a–c ). We also tested other microbiota-modulated metabolites that have implications in different gastrointestinal cancers, such as the secondary bile acid deoxycholic acid (DCA) and the primary bile acid glycocholic acid (GCA) 18 , 19 . In addition, we chose to test two other metabolites that were increased in R patients or R-microbiota-colonized gnotobiotic mice—namely, the indole derivate indole-3-propionic acid (IPA) and hippuric acid—in combination with FIRINOX.…”
Section: -Iaa Induces a Response To Chemotherapymentioning
confidence: 99%
“…3a–c ). We also tested other microbiota-modulated metabolites that have implications in different gastrointestinal cancers, such as the secondary bile acid deoxycholic acid (DCA) and the primary bile acid glycocholic acid (GCA) 18 , 19 . In addition, we chose to test two other metabolites that were increased in R patients or R-microbiota-colonized gnotobiotic mice—namely, the indole derivate indole-3-propionic acid (IPA) and hippuric acid—in combination with FIRINOX.…”
Section: -Iaa Induces a Response To Chemotherapymentioning
confidence: 99%
“…Conjugated bile acid levels (glycocholic acid detected in most cases) are elevated in the plasma and serum samples from PDAC patients compared to controls [58, [95][96][97][98][99]. The levels of unconjugated bile acids in the plasma of PDAC patients are reduced [98].…”
Section: Discussionmentioning
confidence: 99%
“… 122 Likewise, in both PDAC cell lines and human samples, it was found that bile accelerates carcinogenesis through the overexpression of MUC4. 123 In addition to their contribution to pancreatic carcinogenesis via insulin resistance [or elevated insulin-like growth factor 1 (IGF-1) signaling], hyperinsulinemia, and the disruption of the GM in obesity and DM, BAs also elevate the risk of PC via gallstones, pancreatobiliary maljunction, and chronic pancreatitis. 117 , 124 Moreover, BAs can have much more direct and local effects on carcinogenesis.…”
Section: Mechanisms Of Obesity- and Dm-related Pancreatic Carcinogenesismentioning
confidence: 99%